A holistic Fenton oxidation-biodegradation system for treatment of phenol from coke oven wastewater: Optimization, toxicity analysis and phylogenetic analysis. (October 2020) - Tyagi, Megha; Kumari, Nisha; Jagadevan, Sheeja
Graphical abstract: Highlights: Fenton oxidation was carried out for phenol removal from coke oven wastewater. Dual wavelength toxicity analysis was accomplished on Fenton treated samples. Hybrid treatment was conducted by coupling of Fenton oxidation and biodegradation. Phylogenetic analysis was conducted for isolated bacterial strains. Abstract: In this study, the efficacy of a hybrid treatment approach by integrating Fenton's oxidation with biological treatment for removal of phenol from synthetic coke oven wastewater was investigated. Central composite design using response surface methodology was applied to optimize the dose of FeSO4 and H2 O2 with maximum phenol removal and minimum toxicity. Results indicate that 6.3 mM and 20 mM of FeSO4 and H2 O2 respectively, were capable of 74 % degradation of 1000 mg/L phenol, 99.99 % of 100 mg/L of cyanide with 10 % residual toxicity, which was acceptable for the next biological treatment step. On the basis of biodegradation studies it was found that a mixed consortium of three isolated bacterial strains namely BSPS_CN, BSPS_PHE and BSPS_PHE2 were capable of 98.8 % degradation of 300 mg/L phenol, which was remaining after the Fenton treatment. BSPS_PHE2 was found to be the most efficient with 92.45 % phenol removal efficiency. Phylogenetic analysis of cultures indicated that isolates BSPS_PHE and BSPS_PHE2 were genetically most closely related to Pseudomonas species, whereas BSPS_CN was found to be closely related to Enterobacter sp. The 2-step sequential treatment was capable of achieving 99.3 % degradation of 1000 mg/L phenol and complete removal of cyanide (100 mg/L) from coke oven wastewater. Harmonization of Fenton's oxidation with biodegradation makes the treatment method more economical and was found to be an efficient method for removal of recalcitrant compounds from coke oven wastewater.